When and how does leader humor promote customer-oriented organizational citizenship behavior in hotel employees? - Cheng, Bao; Dong, Yun; Kong, Yurou; Shaalan, Ahmed; Tourky, Marwa (Elsevier, 2022)
This study explores whether leader humor can encourage staff to exceed job expectations in their positive behavior toward customers, even in the notoriously stressful context of the hospitality industry. Based on our findings, leaders who use humor are more likely to prompt employees to engage in customer-oriented organizational citizenship behavior (OCB). Leader humor affects customer-oriented OCB through the mediating effect of relational energy. In addition, employee traditionality and relational energy differentiation moderate the process. Using time-lagged data collected from 456 employees in 71 teams in China’s hotel industry, this study adds significant knowledge to the under-researched area of humor and leader humor in the hospitality industry. The findings suggest that hospitality leaders can implement humor to obtain positive effects by raising relational energy and triggering customer-oriented OCB, particularly among less-traditional workers and in situations of low relational energy differentiation.
Keywords: Leader humor; Customer-oriented organizational citizenship behavior; Relational energy; Traditionality; Relational energy differentiation